2010
DOI: 10.1016/j.jmb.2010.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Nucleoside Monophosphate Substrates by Haemophilus influenzae Class C Acid Phosphatase

Abstract: SummaryThe e (P4) phosphatase from Haemophilus influenzae functions in a vestigial NAD + utilization pathway by dephosphorylating NMN to nicotinamide riboside. P4 is also the prototype of class C acid phosphatases, which are nonspecific 5′-, 3′-nucleotidases localized to the bacterial outer membrane. To understand substrate recognition by P4 and other class C phosphatases, we have determined the crystal structures of a substrate-trapping mutant P4 enzyme complexed with NMN, 5′-AMP, 3′-AMP, and 2′-AMP. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Structures of rP4 have shown that the lower part of the active site contains the substrate phosphoryl binding site, which includes an essential Mg 2+ ion surrounded by the four Asp residues of the DDDD motif [9, 15]. The roles of these Asp residues in rPmCCAP can be inferred from structures of rP4 complexed with substrates [15] and more generally, studies of HAD superfamily enzymes [27]. The first Asp (Asp63 in rPmCCAP, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Structures of rP4 have shown that the lower part of the active site contains the substrate phosphoryl binding site, which includes an essential Mg 2+ ion surrounded by the four Asp residues of the DDDD motif [9, 15]. The roles of these Asp residues in rPmCCAP can be inferred from structures of rP4 complexed with substrates [15] and more generally, studies of HAD superfamily enzymes [27]. The first Asp (Asp63 in rPmCCAP, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The estimated free energy of dissociation from PISA (42 kcal/mol) suggests that the dimer is stable in solution. Furthermore, an identical dimer is found in both the tetragonal and hexagonal rP4 crystal lattices [9, 15], and several intersubunit interactions are observed in both enzymes. These conserved interactions include an intersubunit Glu-Arg-Asn electrostatic network that involves an active site loop (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations